2022
DOI: 10.18502/jhs.v9i4.8214
|View full text |Cite
|
Sign up to set email alerts
|

Workload Status and Its Relationship with Job Stress in Nurses during the COVID-19 Pandemic

Abstract: Background and Purpose: Currently, the high prevalence of COVID-19 and increased workload in hospitals has posed a threat to the physical, mental, and emotional health of nurses. The present study was an attempt to investigate the workload and its relationship with job stress of nurses in COVID-19 reference hospitals in southern Iran. Materials and Methods: This descriptive-analytical and cross-sectional study was conducted in 2021 on 431 nurses from COVID-19 reference hospitals in southern Iran. Data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…This condition is one of the triggers for work stress for nurses. Stress at work can affect the hormonal balance and normal physiology of nurses working in hospitals, especially during the Covid-19 pandemic (4).Fear of Covid-19 transmission is also one of the causes of nurses' work stress (1). In addition to fear of infection transmission, excessive workload factors and psychological fatigue resulting from work will also trigger work stress (27).…”
Section: Workloadmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition is one of the triggers for work stress for nurses. Stress at work can affect the hormonal balance and normal physiology of nurses working in hospitals, especially during the Covid-19 pandemic (4).Fear of Covid-19 transmission is also one of the causes of nurses' work stress (1). In addition to fear of infection transmission, excessive workload factors and psychological fatigue resulting from work will also trigger work stress (27).…”
Section: Workloadmentioning
confidence: 99%
“…In dealing with this pandemic condition, health service units, especially hospitals, are required to be able to provide adequate resources in treating and controlling the transmission of Covid-19. The high prevalence of Covid-19 and the increased workload in hospitals pose a threat to the physical, mental, and emotional health of nurses (1). During the Covid-19 pandemic, the role of nurses is very important in preparing health services and reducing the spread of Covid-19.…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, a total of 7,040,467 confirmed cases and 136,631 deaths due to COVID-19 were reported (4). This disease has posed major challenges to individuals' physical and mental health due to its rapid spread (5). Healthcare workers (HCWs) who are at the forefront of combating COVID-19 are exposed to an increased risk of infection due to long and uncomfortable work shifts and increased workload to save patients' lives (6).…”
Section: Introductionmentioning
confidence: 99%
“…A study from China indicated that in the first stage of the COVID-19 pandemic, infected nurses accounted for 29% of all hospitalized cases with COVID-19 (7). In Iran, at least 40 HCWs died due to COVID-19, and hundreds of them have been hospitalized after the onset of symptoms (5). Evidently, the safety of the HCWs is not only crucial for protecting them against the virus but is also effective in preventing the transmission of the virus (8).…”
Section: Introductionmentioning
confidence: 99%
“…Conforme relatório da Organização Mundial da Saúde (OMS) (2016), centenas de milhões de pessoas são afetadas por infecções relacionadas à assistência à saúde (IRAS), todos os anos, mundialmente, considerado um problema de saúde pública sem precedência. Mediante a gravidade, para melhor compreensão, define-se IRAS, como adquiridas durante o processo de cuidado, que podem acontecer no intervalo de 48 horas da admissão do paciente ou manifestar após a alta, com exceção, nos procedimentos cirúrgicos sem e com implantes de próteses que se estende até 30 e 90 dias respetivamente (HESPANHOL et al, 2019;KHAMMARNIA et al, 2021).…”
Section: Introductionunclassified